Cognitive leisure activities and future risk of cognitive impairment and dementia: systematic review and meta-analysis. (9th August 2016) - Yates, Lauren A; Ziser, Shier; Spector, Aimee; Orrell, Martin
ABSTRACT: Background: As life expectancies continue to rise, modifiable lifestyle factors that may prevent cognitive decline and dementia in later life become increasingly important in order to maintain quality of life in old age. Methods: Five meta-analyses were conducted on data from papers identified in a systematic review. Studies were grouped according to outcomes (dementia, cognitive impairment including amnestic Mild Cognitive Impairment (aMCI), Mild Cognitive Impairment (MCI), and cognitive decline) and output (risk (RR), odds (OR), or hazard ratios (HR)). Results: Nineteen studies met our inclusion criteria and quality assessments. Four of five meta-analyses showed significant associations between participation in cognitive leisure activities and reduced risk of cognitive impairment (OR = 0.69, 95% CI: 0.56–0.85) and dementia (HR = 0.58, 95% CI: 0.46–0.74; RR = 0.61, 95% CI: 0.42–0.90; OR = 0.78, 95% CI: 0.67–0.90). However, one pooled analysis of cognitive impairment studies did not reach significance (HR = 0.85, 95% CI: 0.71–1.02). Mentally stimulating leisure activities were significantly associated with later life cognition (β = 0.11, p = 0.05), better memory (β = 0.20, 95% CI: 0.11–0.29), speed of processing (β = 0.37, 95% CI: 0.29–0.45), and executive functioning (β = 0.23, 95% CI: 0.15–0.29), and less decline in overall cognition (β = −0.23, p < 0.01), language (β = −0.11, p < 0.05), and executive functioning (β = −0.13, p < 0.05). Activities were also shown to reduce rate of cognitive decline (estimate = 0.03, SE = 0.01, p = 0.00). Conclusions: There is increasing evidence that participation in cognitively stimulating leisure activities may contribute to a reduction of risk of dementia and cognitive impairment in later life. Promoting involvement in such activities across lifespan could be an important focus for primary prevention strategies for governments and health services.